The Digital Wallet Revolution: An Empirical Analysis of Its Effects on Mental Accounting and Financial Practices - Novie Susanti Suseno; Hilmi Aulawi (Khazanah Sosial, 2024)
In the current digital era, digital wallets have become an important innovation. This can certainly change the way individuals manage finances. This research aims to examine the influence of using digital wallets on mental accounting and its impact on financial behavior. A quantitative approach using the SEM method was used in this research to obtain more measurable, structured, and objective results. The data collection technique is through distributing questionnaires. Respondents in this research are the millennial generation born in 1981-1996 who have used digital wallets in West Java. The selection of West Java as a research location was based on the significant increase in the use of digital wallets in this area, which is affecting various aspects of daily life. The total sample was 300 respondents using the cluster sampling technique. The analytical method used is Structural Equation Modeling (SEM). The research results show that digital wallets influence mental accounting, and mental accounting influences financial behavior. Apart from that, the implications of the research results show that digital wallet users must take advantage of existing features to improve financial management, achieve financial goals, and reduce stress. Furthermore, service providers need to continue to innovate with features such as detailed financial reports, budget reminders, and spending analysis, as well as educate users so they can use these features optimally to increase satisfaction and loyalty.